Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/6372572
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combination Co-Kriging Model Based on Gaussian Random Process

Abstract: Co-Kriging (CK) modeling provides an efficient way to predict responses of complicated engineering problems based on a set of sample data obtained by methods with varying degree of accuracy and computation cost. In this work, the Gaussian random process (GRP) is introduced to construct a novel combination CK model (CK-GRP) to improve the prediction accuracy of the conventional CK model, in which all the sample information provided by different correlation models is well utilized. The features of the new model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Based on visual inspection and quantitative appraisal both for interpolated values and standard errors, it is suggested that CK (with soil cohesion as covariate) performs better than IDW and OK in estimating spatial distribution of soil depth to hardpan in Western Central Java. This is consistent with the aim of Cokriging model development (Myers 1984) and its implementation 5 (Minnitt and Deutsch 2014;Adhikary et al 2017;Xie et al 2018).…”
Section: Interpolation Performancesupporting
confidence: 82%
“…Based on visual inspection and quantitative appraisal both for interpolated values and standard errors, it is suggested that CK (with soil cohesion as covariate) performs better than IDW and OK in estimating spatial distribution of soil depth to hardpan in Western Central Java. This is consistent with the aim of Cokriging model development (Myers 1984) and its implementation 5 (Minnitt and Deutsch 2014;Adhikary et al 2017;Xie et al 2018).…”
Section: Interpolation Performancesupporting
confidence: 82%
“…Kriging has many advantages; such as being a proper approach to multi-dimensional problems and its prediction capability as compared to other metamodeling techniques [31][32] and being able to produce error estimates. On the other hand, Kriging technique is still developing by many research groups from all around the world [33][34][35][36][67][68]. Those development studies are rather concentrate on the sampling types [37], on the tuning parameter exploration such as variogram adaptation [38] or on adding some descriptive new information into the algorithm such as gradient/hessian enhanced types [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%